(untitled) (Research, Society and Development, 2021)
The present study evaluated the influence of algal biomass of post-treatment of domestic sewage in different polishing ponds. For this purpose, the research was carried out at the Experimental Station for Biological Treatment of Sanitary Sewers (EXTRABES), located in the city of Campina Grande-PB, in two experimental phases. In the first phase, the experimental system consisted of four lagoons, in which two were monitored with continuous feeding (LC57 and LC45) and two with semi continuous feeding (LB57 and LB45). In the second experimental phase, the performance of three lagoons fed in batches (LBT45 and LB245), and one fed continuously (LC245) was evaluated. It was found that the determination of chlorophyll-a concentrations could provide an estimate of phytoplankton biomass, however, they were easily altered, due to variations in high light incidence, temperature, organic charge and HRT. It was observed that the digested effluent and the algae biomass from the overflow pond with 2.4-day HDT in the first phase of the study, provided a greater development of the phytoplankton community. During the second phase, the polishing ponds fed in sequential batches (LB245 and LBT45) showed higher concentrations of chlorophyll-a compared to the previous experimental phase. It was concluded that the polishing ponds fed in batch regime stood out for presenting superior removals to the ponds with continuous and semi continuous feeding, showing them as promising in the treatment of domestic sewage. In addition to obtaining excellent results, mainly in the removal of nutrients, it was possible to treat a larger amount of affluent in less time of operation.